2015
DOI: 10.15537/smj.2015.7.11026
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cigarette smoking on morphological features of platelets in healthy men

Abstract: Objectives:To assess the effects of cigarette smoking on thrombocytopoiesis and some platelet morphological parameters in healthy male smokers.Methods:In this cross-sectional study, 542 consecutive healthy men (aged 20 to 88 years), referred to the laboratory of Fatemieh Hospital, Semnan, Iran, between November 2011 and November 2012 for checking up were enrolled. The subjects were divided into 2 groups of smokers (n=258 with frequency of 10 or more cigarette per day with more than 12 months duration of smokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 24 publications
1
15
1
Order By: Relevance
“…This result was in the line with the ROA Mustafa study, 15 that, smoking significantly reduced platelet count (212.30±55.71 vs. 238.23±36.89×10 9 /l) and previous study carried out by Metta S et al, 16 in 2015 reported that, platelet count was significantly lower in chronic smokers. The current results was not in agreement with the findings stated by Ghahremanfard et al, 17 who concluded that, the mean platelet count was significantly higher in adult smokers than in adult non-smokers and Al-Dahr study, 18 reported that, no significant difference between adult smokers and non-smokers regarding platelet count. Concerning PT the current study revealed that, the mean PT was significantly shorter in smokers when compared to the non-smokers, (12.9±1.15s versus 13.7±1.04s, p <0.000), the significantly reduced PT value was agreed with the results obtained by Akpotuzor et al, 19 who reported that, mean prothrombin time values of smokers were significantly lower when compared with the non-smokers and disagree with the findings obtained from the study carried out by Metta S et.al, 16 who showed that no significant difference in PT, on the other hand the current study results regarding PT value inconsistent with the results of Al-Dahr study, 18 who reported that PT was not changed significantly in the smoker groups.…”
Section: Discussioncontrasting
confidence: 99%
“…This result was in the line with the ROA Mustafa study, 15 that, smoking significantly reduced platelet count (212.30±55.71 vs. 238.23±36.89×10 9 /l) and previous study carried out by Metta S et al, 16 in 2015 reported that, platelet count was significantly lower in chronic smokers. The current results was not in agreement with the findings stated by Ghahremanfard et al, 17 who concluded that, the mean platelet count was significantly higher in adult smokers than in adult non-smokers and Al-Dahr study, 18 reported that, no significant difference between adult smokers and non-smokers regarding platelet count. Concerning PT the current study revealed that, the mean PT was significantly shorter in smokers when compared to the non-smokers, (12.9±1.15s versus 13.7±1.04s, p <0.000), the significantly reduced PT value was agreed with the results obtained by Akpotuzor et al, 19 who reported that, mean prothrombin time values of smokers were significantly lower when compared with the non-smokers and disagree with the findings obtained from the study carried out by Metta S et.al, 16 who showed that no significant difference in PT, on the other hand the current study results regarding PT value inconsistent with the results of Al-Dahr study, 18 who reported that PT was not changed significantly in the smoker groups.…”
Section: Discussioncontrasting
confidence: 99%
“… 1 Recently, the role of cigarette smoking in abnormalities in platelet activation and aggregation, along with other coagulation processing disruptions resulting in thrombotic formations, has been suggested. 2 In smokers, the endothelial lining is damaged, which causes platelets to adhere to the subendothelial collagen and therefore, the number of platelets in circulation might vary. There have been conflicting results in previous studies on the effect of smoking on platelet counts.…”
Section: Introductionmentioning
confidence: 99%
“…We suggest that the dose of ASA should be kept at twice a day in patients with higher anticipated turnover, such as smokers or diabetics. 26 27 …”
Section: Discussionmentioning
confidence: 99%